2020
DOI: 10.1128/jcm.00272-20
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of QuantiFERON-TB Gold Plus Test for Diagnosis of Mycobacterium tuberculosis Infection in Children

Abstract: Compared to its predecessor QuantiFERON-TB Gold In Tube (QFT-IT), QuantiFERON-TB Gold Plus (QFT-Plus) contains an additional antigen tube (TB2), stimulating both CD4+ and CD8+ T cells. The ability to discriminate CD4+ and CD8+ responses is suggested to be useful in differentiating stages of Mycobacterium tuberculosis infection. While QFT-Plus has already been evaluated in adults, there are not enough data in children evaluated for suspected active tuberculosis (TB) or latent TB infection (LTBI). A prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…Other clinical studies, however, showed no significant difference in the proportion of positive results between TB1 and TB2 tubes ( 23 ). Fifteen clinical studies comparing QFT-Plus to QFT-GIT were recently reviewed ( 24 ).…”
Section: Discussionmentioning
confidence: 94%
“…Other clinical studies, however, showed no significant difference in the proportion of positive results between TB1 and TB2 tubes ( 23 ). Fifteen clinical studies comparing QFT-Plus to QFT-GIT were recently reviewed ( 24 ).…”
Section: Discussionmentioning
confidence: 94%
“…They had no history of human immunodeficiency virus infection. It is worth noting that the QFT-Plus test, in addition to being highly sensitive in detecting active TB in the elderly and in immunocompromised subjects, also displayed good sensitivity in identifying TBI in children, whose immune systems are not fully mature [30,31]. Unlike other IGRAs, QFT-Plus quantifies the immune response mediated by both CD4 and CD8 T cells following M. tuberculosis antigenic induction.…”
Section: Discussionmentioning
confidence: 99%
“…One of the shortages was neither TST nor IGRAs can effectively discriminate active TB from latent TB infection 46 . Recently, research showed that QuantiFERON‐TB Gold Plus Test showed good sensitivity for active TB and was particularly useful for the evaluation of children with suspected latent TB infection 47 …”
Section: Discussionmentioning
confidence: 99%